A sensibilização sobre o acolhimento: uma proposta interventiva com a criação de rapsódias do cotidiano infantil - Franco, Merilis Aparecida (2021)
The purpose of this research is to host a Child Education Center (CEC). It seeks to answer the following question: How is it possible to create strategies to sensitize teachers about the importance of day-to-day care? Its general objective is to create strategies to make teachers aware of the importance of welcoming. As specific objectives, we list the following: registering daily memories of Early Childhood Education, reflecting on the dilemmas when welcoming babies and young children, elaborating narratives (daily rhapsodies) as a strategy for raising awareness and reflection for the teachers who work in the CEC, list theoretical items to broaden the view on welcoming. The hypothesis is that the teachers who welcome babies and young children need constant theoretical knowledge about the importance of this day-to-day care at the CEC; as well as reflections on the practice, through rhapsodies and narratives about the affective relationships between teachers, babies and young children. The universe of research is a Center for Early Childhood Education, located in the city of São Paulo, located in the East Zone, which serves 115 children from 0 to 4 years of age. The participating subjects are three teachers from the nursery I group (0 to 9 months), the nursery II group (10 months to 01 year and 8 months), and mini group II (02 years and 9 months to 4 years). The methodology used is of a qualitative nature and the data collection instrument is the daily narratives. The analyzes are made through three daily narratives with regard to welcoming. To support the Theory of Attachment category, we used the following authors: John Bowlby, Donald Winnicott, Judith Falk, Emmi Pikler and Carlina Rinaldi; for the category of Early Childhood Education teacher, we used Sonia Kramer and Zilma de Moraes Ramos de Oliveira; to support the category of narratives we look at the studies by Sousa and Cabral; on daily rhapsodies, as an intervention proposal, we used the studies of Paulo Fochi; to support the methodology, Lüdke and André. We also analyzed some current federal and municipal laws that govern early childhood education. The results confirm our hypothesis, that is, the teachers who welcome babies and young children need constant theoretical knowledge about the importance of this daily reception in the CEI; as well as reflections on the practice, through rhapsodies and narratives about the affective relationships between teachers, babies and young children. It is worth remembering that the concepts of attachment figures and attachment behavior are not substantially covered in official documents, nor in the academic training of teachers. The notions that involve care, movement and free play, developed from a listening that favors the dialogue between educator and child, and how these elements influence the formation of attachment relationships, are little discussed in the network training offered by the municipality from São Paulo. The intervention proposal aims to contemplate such reflections on the dilemmas of children's daily lives, using narratives/rhapsodies, strategies to raise awareness of the importance of welcoming.